Flow Pattern And Hydraulic Characteristics A Of Hexagonal Modular As Channel Bed - Abu Seman @ Hj Ahmad, Nor Amirah (2019)
Studies have shown that sustainable designs such as Sustainable Drainage Systems (SUDS) would help mitigate some of these effects sustainable. SUDS is natural drainage systems that simulate the natural drainage of a catchment and work in harmony to achieve an increase in ground infiltration and treatment of runoff; and a reduction in flow rates and volume of surface runoff, improving biodiversity and ultimately improving sustainability. However, the sustainability of SUDS devices is questionable because their component parts involve the use of natural resources. This study proposed the application newly designed namely Green Drainage System (GDS) using HM as channel bed. Therefore, it is important to determine the hydraulic characteristic of this module focusing on HM. This thesis investigated experimentally using tilting flume channel and rig simulator. HM as a bed channel was tested at three different slopes of 0.002, 0.005 and 0.008 and each slope consists of four different discharges. In order to verify the results of experimental measurements of the flume channel, the numerical modeling for all the cases was considered, under the same operating conditions with experimental measurements using porous media models and turbulence model (FLOW3D). Results agreed that the experimental and numerical results show good agreement. The maximum flow velocity occurs near the water surface with an increasing flow velocity at increasing depth. The steeper the slopes shows higher maximum water velocity near the water surface emphasized toward the end of flume channel. HM as the effect of porous bed on the turbulent characteristics of the flow in an open channel is different in comparison with the impermeable bed. The velocities are reduced with the decreasing of the water level due to the greater influence of the HM on the flow above the porous bed. It is apparent that the order of reduction velocity porous bed with HM >porous bed without HM > impermeable bed.